2020
DOI: 10.1080/2162402x.2020.1824323
|View full text |Cite
|
Sign up to set email alerts
|

Bispecific antibody approach for EGFR-directed blockade of the CD47-SIRPα “don’t eat me” immune checkpoint promotes neutrophil-mediated trogoptosis and enhances antigen cross-presentation

Abstract: Helfrich (2020) Bispecific antibody approach for EGFR-directed blockade of the CD47-SIRPα "don't eat me" immune checkpoint promotes neutrophil-mediated trogoptosis and enhances antigen cross-presentation, OncoImmunology, 9:1, 1824323,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 33 publications
0
33
0
Order By: Relevance
“…We previously reported that the capacity of bsAb CD47xEGFR-IgG2s to internalize CD47 dose-dependently relied on the cell surface expression levels of EGFR of the respective cancer cell lines. 8 In particular, bsAb CD47xEGFR-IgG2s showed only low capacity for CD47 internalization when treating EGFR low cell lines like OvCAR-3 and PC-3, but prominent capacity to do so when treating EGFR high cell lines like NCI-H292, FaDu, A431 and SK-RC-52 cells as is shown in Suppl. Figure S4A-C.…”
Section: Resultsmentioning
confidence: 91%
See 4 more Smart Citations
“…We previously reported that the capacity of bsAb CD47xEGFR-IgG2s to internalize CD47 dose-dependently relied on the cell surface expression levels of EGFR of the respective cancer cell lines. 8 In particular, bsAb CD47xEGFR-IgG2s showed only low capacity for CD47 internalization when treating EGFR low cell lines like OvCAR-3 and PC-3, but prominent capacity to do so when treating EGFR high cell lines like NCI-H292, FaDu, A431 and SK-RC-52 cells as is shown in Suppl. Figure S4A-C.…”
Section: Resultsmentioning
confidence: 91%
“…In this respect, we previously reported on bsAb CD47xEGFR-IgG1 which has potent capacity to selectively direct CD47-blockade toward EGFR-overexpressing cancer cells. 8 BsAb CD47xEGFR-IgG1 has a unique mode-of-action in that treatment of CD47 pos /EGFR pos cancer cells resulted in rapid co-internalization of EGFR and CD47, followed by prolonged displacement of both EGFR and CD47 from the cell surface. For the current study, we constructed variant bsAb CD47xEGFR-IgG2s which was equipped with an immune effector function nullified Fc domain.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations